The Concept of Corporate Criminal Liability in the Fisheries Sector After the Job Creation Law Application - Hudi, Nurul; Muhadar, Muhadar; Yudianto, Otto (Jurnal Dinamika Hukum, 2023)
Various kinds of criminal acts in the field of fisheries have emerged, consisting of individuals and or corporations. The existence of a corporation is an obstacle in determining criminal responsibility. The purpose of this research is to analyze the concept of corporate criminal liability in the fisheries sector. The research method used is normative juridical with statutory and conceptual approaches. The results of the study found differences in the concept of corporate criminal responsibility after the Application of the Job Creation Law where previously criminal acts of fishing could be carried out by corporations, and criminal responsibility was carried out by administrators. After the enactment of the Job Creation Law, the concept of corporate criminal responsibility for fisheries follows the development of the third stage of corporate criminal responsibility, in which the corporation commits a crime against the responsible corporation.